Covered distances analysis of brasilian professional soccer players obtained by an automatic tracking method - - Misuta, M. S.; Menezes, R. P.; Moura, F. A.; Figueroa, J. P.; Cunha, S. A.; Leite de Barros, R. M. (ISBS - Conference Proceedings Archive (Konstanz), 2006)
The aim of this study is to present and analyse the covered distances of soccer players obtained automatic and simultaneously. Four matches of eight different teams of the Brazilian 1st Division Soccer Championship were filmed. Applying a previously developed automatic tracking method, the results of 55 outline players who participated in the whole game (n=55 players) are presented. The results of mean covered distance and standard deviations after 90 minutes are 10,012 ± 1,024 m. The mean covered distance in the 1st half was 5,173 m (± 394 m) highly significantly longer (p<0.01) than the mean 4,808 m (± 375 m) in the 2nd half time. Comparing the median covered distance minute-to-minute in both periods, the statistical tests revealed that after the fifth minute the data from 1st half presented highly significant differences compared to the data of the 2nd half. These results are compared with the findings of previous studies.